Effect of betel and lemon aqueous extracts on clinical isolates of Escherichia coli (Eastern Journal of Medical Sciences, 2017)
Escherichia coli causes a plethora of human infections and can be difficult to treat due to biofilm formation and high degree of antibiotic resistance. Hence, natural inhibitory compounds are being studied against this pathogen. Our study evaluated the inhibitory role of paan leaf and lemon on this pathogen. Both paan leaf and lemon juice showed inhibition of growth and virulence factors at 4 g% concentration. This can show the road for further studies to characterize these inhibitory natural moieties.